Quintilian on the Teaching of Speaking and Writing : Translations from Books One, Two, and Ten of the "Institutio oratoria" - Quintilian (Book collections on Project MUSE., 2016)
"Translation, with introductory material and other critical apparatus, of 'Institutio oratoria' (The Education of the Orator), by Roman rhetor Quintilian (Marcus Fabius Quintilanus, ca. A.D. 35-98?)."--